THE VARIABLE GEOMETRY OF COPYRIGHT AND AI IN THE EUROPEAN AND ISLAMIC LEGAL LANDSCAPES - Rebecca-Georgia DUNCA (Challenges of the Knowledge Society)
Copyright protection, the cornerstone of intellectual property rights in the modern legal landscape, is likely to be subject to unique considerations and challenges when viewed through the prism of the European and Islamic legal systems. In addition, rapid advances in AI technology further complicate the legal framework of copyright in the context of European case-law and Islamic jurisprudence. This article explores, ab initio, the complex interplay between copyright protection in the light of European and Islamic law, respectively the legal implications of AI on copyright, drawing on classic European and Islamic legal sources and, intrinsically, contemporary research. In the context of Islamic law, the fundamental principles of copyright are based on the broader Islamic legal framework, which emphasises justice, fairness, and the protection of intellectual creations. Islamic jurisprudence recognises the inherent value of intellectual endeavour and encourages the protection of creative works. In general, copyright protection, as an avatar of intellectual property, is acceptable under Islamic law due to the absence of any express statement to the contrary in the Quran or Sharia. On the other hand, the absence of explicit provisions for AI-generated content in traditional Islamic legal texts raises questions about the adaptability of Islamic law to the dynamic AI landscape. European legislation, on the other hand, has evolved to address copyright issues from an AI perspective through a combination of legislative initiatives and court rulings. Directive (EU) 2019/790 on copyright and related rights in the digital single market, in particular art. 17, sought to make online platforms liable for copyright infringement by introducing content filtering and licensing mechanisms. European courts have also been confronted with issues relating to AI-generated works, highlighting the need to strike a balance between the rights of creators and the potential of AI to contribute to the public domain. Therefore, this article also aims to analyse the convergences and divergences between Islamic and European legal perspectives on copyright in the context of AI, with a view to highlighting commonalities in terms of recognising the value of intellectual creations and the importance of encouraging innovation. At the same time, throughout the article, the differences between legal mechanisms will be discussed, with European law taking a more proactive regulatory approach and Islamic law relying on general principles that may need to be adapted to meet the challenges posed by AI and its growing trend.